"Beer is more efficient than social media"—Political parties and strategic communication in Austrian and Swiss national elections. Issue 4 (2nd October 2017) - Klinger, Ulrike; Russmann, Uta
ABSTRACT: We investigate political parties´ social media strategies, their perceived effectiveness, and how social media campaigns are internally organized. Our study focuses on Austria and Switzerland, countries with consociational political systems with less competitive elections and less personalization. The paper is based on semistructured interviews with all parties in Austrian and Swiss parliaments after the national elections in 2011 and 2013, when, for the first time, all parties employed social media in their campaigns. Our findings support a skeptical perspective regarding social media's perceived significance and effects.